Towards an agroecology of the Roman expansion: Republican agriculture and animal husbandry in context -- Supplemental Tables - Trentacoste, A; Lodwick, L (University of Oxford, 2022)
Supplemental tables to Trentacoste, A. and Lodwick, L. (2023) Towards an agroecology of the Roman expansion: Republican agriculture and animal husbandry in context. In S. Bernard, L. Mignone and D. Padilla Peralta (eds), Making the Middle Republic: New Approaches to Rome and Italy, 400-200 BCE. Cambridge University Press, Cambridge.